2013
DOI: 10.1111/wrr.12051
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes impairs adipose tissue–derived stem cell function and efficiency in promoting wound healing

Abstract: Adipose tissue-derived stem cells (ASCs) are gaining increasing consideration in tissue repair therapeutic application. Recent evidence indicates that ASCs enhance skin repair in animal models of impaired wound healing. To assess the therapeutic activity of autologous vs. allogeneic ASCs in the treatment of diabetic ulcers, we functionally characterized diabetic ASCs and investigated their potential to promote wound healing with respect to nondiabetic ones. Adipose tissue-derived cells from streptozotocin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
160
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 41 publications
(108 reference statements)
8
160
3
1
Order By: Relevance
“…Furthermore, after obtaining autologous ASCs, ASC sheet preparation requires several weeks. rASCs from diabetic animals exhibit altered properties and impaired functions (40). In fact, our group attempted to create rASC sheets using rASCs from ZDF rats, but cell proliferation was slow (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, after obtaining autologous ASCs, ASC sheet preparation requires several weeks. rASCs from diabetic animals exhibit altered properties and impaired functions (40). In fact, our group attempted to create rASC sheets using rASCs from ZDF rats, but cell proliferation was slow (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In the skin, for example, population-based studies of transplanted diabetic adipose-derived stem cells (ASCs) from mice demonstrate decreased proliferation, migration, and growth factor production, with an inability to promote keratinocyte and fibroblast proliferation and migration. 66 However, stem cells and progenitor cells are complex cell populations associated with functional heterogeneity. Traditional population-level assays, such as microarray or immunoblotting, that involve pooling of RNA or protein from hundreds of thousands of cells report aggregate expression of data.…”
Section: Single-cell Studies Reveal Progenitor Cell Subpopulation Defmentioning
confidence: 99%
“…While taken together, these studies have shown that cellularizing tissue-engineered grafts significantly improves the patency and regeneration over their acellular counterparts; these models hold limited relevance for clinical translation since in practice, cells would need to be harvested from patients at high cardiovascular risk such as diabetics 64,65 and the elderly. [66][67][68] In addition, these high-risk groups possess pathologic conditions such as a hyperglycemic environment [69][70][71][72] and ageassociated senescence, [73][74][75][76][77][78][79][80][81][82][83][84][85] respectively, which can decrease the ability of their stem cells to proliferate, differentiate into specific mesenchymal cell types, and promote angiogenesis. Whereas bone marrow has been shown to be a source of stem cells, it is particularly important to consider the use of adipose-derived mesenchymal stem cells (AD-MSCs) due to their ease of isolation and abundance.…”
Section: Introductionmentioning
confidence: 99%